Entomological assessment of hessian fabric transfluthrin vapour emanators as a means to protect against outdoor-biting Aedes after providing them to households for routine use in Port-au-Prince, Haiti. - Chicoye Supreme; Obrillant Damus; Joseph Frederick; Jean-Frantz Lemoine; Christian Raccurt; Justin McBeath; Nosrat Mirzai; Sheila B Ogoma; Vincent Corbel; Daniel Impoinvil; Gerry F Killeen; Cyrille Czeher (PLoS ONE)
Background A simple treated fabric device for passively emanating the volatile pyrethroid transfluthrin was recently developed in Tanzania that protected against nocturnal Anopheles and Culex mosquitoes for several months. Here these transfluthrin emanators were assessed in Port-au-Prince, Haiti against outdoor-biting Aedes. Methods Transfluthrin emanators were distributed to participating households in poor-to-middle class urban neighbourhoods and evaluated once every two months in terms of their effects on human landing rates of wild Aedes populations. A series of three such entomological assessment experiments were conducted, to examine the influence of changing weather conditions, various transfluthrin formulations and emanator placement on protective efficacy measurements. Laboratory experiments assessed resistance of local Aedes aegypti to transfluthrin and deltamethrin, and the irritancy and repellency of the transfluthrin-treated fabric used in the field. Results Across all three entomological field assessments, little evidence of protection against wild Ae. aegypti was observed, regardless of weather conditions, transfluthrin formulation or emanator placement: A generalized linear mixed model fitted to the pooled data from all three assessment rounds (921 females caught over 5129 hours) estimated a relative landing rate [95% Confidence interval] of 0.87 [0.73, 1.04] for users of treated versus untreated emanators (P = 0.1241). Wild Ae. aegypti in this setting were clearly resistant to transfluthrin when compared to a fully susceptible colony. Conclusions Transfluthrin emanators had little if any apparent effect upon Aedes landing rates by wild Ae. aegypti in urban Haiti, and similar results have been obtained by comparable studies in Tanzania, Brazil and Peru. In stark contrast, however, parallel sociological assessments of perspectives among these same end-users in urban Haitian communities indicate strong satisfaction in terms of perceived protection against mosquitoes. It remains unclear why the results obtained from these complementary entomological and sociological assessments in Haiti differ so much, as do those from a similar set of studies in Brazil. It is encouraging, however, that similar contrasts between the entomological and epidemiological results of a recent large-scale assessment of another transfluthrin emanator product in Peru, which indicate they provide useful protection against Aedes-borne arboviral infections, despite apparently providing only modest protection against Aedes mosquito bites.